2017
DOI: 10.1017/s0954579417001304
|View full text |Cite
|
Sign up to set email alerts
|

Exploring longitudinal associations between neighborhood disadvantage and cortisol levels in early childhood

Abstract: Children who grow up in poverty are more likely to experience chronic stressors that generate “wear” on stress regulatory systems including the hypothalamus– pituitary–adrenal (HPA) axis. This can have long-term consequences for health and well-being. Prior research has examined the role of proximal family and home contributions to HPA axis functioning. However, there is evidence to suggest that more distal levels of context, including neighborhoods, also matter. Prior evidence has primarily focused on adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 69 publications
3
23
0
Order By: Relevance
“…Going beyond individual experiences of adversity and individual socioeconomic status, theory and evidence have suggested that the neighborhoods in which people reside are also fundamental contexts for understanding the biological embedding of social circumstances and accounting for effects on physical health and well-being (Aneshensel, 2009; Bosma et al, 2001; Causadias, 2013; Diez Roux, 2003; Finegood et al, 2017; Hill, Ross, & Angel 2005; Lei et al, 2016, 2017a; Ross & Mirowsky, 2001). This is due to the fact that individuals residing in socio-economically disadvantaged neighborhoods are exposed to a constellation of social stressors associated with increased presence of social disorder and subculture (Anderson, 1999; Burt, Lei, & Simons, 2017; Hill et al, 2005; Latkin & Curry, 2003; Ross & Mirowsky, 2009).…”
mentioning
confidence: 99%
“…Going beyond individual experiences of adversity and individual socioeconomic status, theory and evidence have suggested that the neighborhoods in which people reside are also fundamental contexts for understanding the biological embedding of social circumstances and accounting for effects on physical health and well-being (Aneshensel, 2009; Bosma et al, 2001; Causadias, 2013; Diez Roux, 2003; Finegood et al, 2017; Hill, Ross, & Angel 2005; Lei et al, 2016, 2017a; Ross & Mirowsky, 2001). This is due to the fact that individuals residing in socio-economically disadvantaged neighborhoods are exposed to a constellation of social stressors associated with increased presence of social disorder and subculture (Anderson, 1999; Burt, Lei, & Simons, 2017; Hill et al, 2005; Latkin & Curry, 2003; Ross & Mirowsky, 2009).…”
mentioning
confidence: 99%
“…The present study is an important contribution to a growing body of literature regarding the effects of poverty-related adversity on infant CORT activity (Blair et al, 2008; Blair et al, 2011a; Blair et al, 2011b; Blair, Berry, Mills-Koonce, Granger, & Investigators, 2013; Braren et al, 2019; Clearfield, Carter-Rodriguez, Merali, & Shober, 2014; Finegood et al, 2017; Hill-Soderlund et al, 2015). Namely, we report evidence that early-life poverty-related adversity is associated with elevated CORT levels across infancy.…”
Section: Discussionmentioning
confidence: 76%
“…Decades of research have converged on findings that environmental adversity, such as low socioeconomic status (SES) and poverty, can “get under the skin” in early life to shape the development of infant behavior and physiology (Blair & Raver, 2016; Finegood, Rarick, & Blair, 2017; Frankenhuis & Nettle, 2019; Hackman & Farah, 2009; Herzberg & Gunnar, 2019; Lipina & Posner, 2012). Early development appears to be particularly vulnerable to the effects of adversity, as evidenced by sensitive period research involving both human studies (Davidson & McEwen, 2012; Feldman, 2015; Masten & Cicchetti, 2010) and animal experiments explicating underlying causal mechanisms (Cameron, 2001; Curley & Champagne, 2016; Opendak & Sullivan, 2016; Roth & Sweatt, 2011; Upton & Sullivan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to parental and household factors, an additional level of the environment to consider is the neighbour -hood. Disadvantaged neighbourhoods are linked to worse physical and mental health (Diez Roux & Mair, 2010), child verbal ability (Sampson, Sharkey, & Raudenbush, 2008), educational attainment (Boyle, Georgiades, Racine, & Mustard, 2007), cortisol functioning (Finegood, Rarick, Blair, & Investigators, 2017;Karb, Elliott, Dowd, & Morenoff, 2012;Theall, Shirtcliff, Dismukes, Wallace, & Drury, 2017), and adult cognitive functioning (Shih et al, 2011;Wight et al, 2006). Furthermore, given the relevance of assessing the experience of SES, it is important to consider families' perceptions of where they live.…”
Section: Neighbourhood Chaosmentioning
confidence: 99%